Qualidade da água e poder de depuração do rio Marrecas em seu médio e baixo curso - Biguelini, Cristina Poll (2013)
The scarcity of water quality and concern for their management occurs in a more decentralized as possible is one of the biggest problems of today and would not be different in the municipality of Francisco Beltrão, that due to the large and rapid urban development, has become the most populous southwestern region of Paraná. Situation that was derived in an apparent degradation of the river Marrecas with wide decrease in vegetation cover, and several irregular housing effluent releases (many illegal).We tried to monitor the quality of the river in its middle reaches Marrecas, verifying the levels of pollution, eutrophication and the power to purify contamination suffered in the urban area, three monitoring points (before and after the urban area and near its mouth), by means of physico-chemical and microbiological control carried out seasonally, between higher and lower rainfall (August-October 2011), diagnosing the current situation through the classification methodology "Quality Index of waters "(ANA, 2005), for taking corrective and preventive actions in the future. These variables were associated with the results of flow and rainfall for the period. The results showed that some variables are analyzed in situ, showed normal values and other surpass the limits stipulated by law. The index of the final water quality varied between the range of "bad" to "regular" in August 2011, and between "bad" to "good" in October. The trophic state index ranged from eutrophic, mesotrophic and supereutrófico. The power of purification of the river, we used the variables BOD, COD and OD values were compared between the two point tracking (outside the city) and paragraph 3 of monitoring (near the mouth), concluding that in August the river could not debug the load of pollutants, but in October the debugging process was observed.